Morocco - Moulaison, Heather Lea (Université d'Ottawa | University of Ottawa, 2011)
The Kingdom of Morocco is a developing country in the western part of North Africa. Moroccans are largely Muslim Arabs who respect tradition. Access to information can be gained through kinship networks and other affinity relationships cultivated by Moroccans. Traditional social networks make use of time-honored methods of communicating. Increasingly, they also use modern Information and Communication Technologies (ICTs).
Keywords: morocco; social networking